#Smiling, #venting, or both? Adolescents' social sharing of emotions on social media. (July 2018) - Vermeulen, Anne; Vandebosch, Heidi; Heirman, Wannes
Abstract: Although social media offer adolescents new possibilities for emotion regulation, little is known about how adolescents use different platforms to this end. This study adds to the emotion regulation literature and affordances-of-technologies perspective by describing whether and how adolescents use different social media platforms (Facebook, Instagram, Snapchat, Twitter, Tumblr, YouTube, 9Gag, and blogs) for emotion sharing and how technical, social, and contextual factors influence these practices. In-depth interviews with 22 adolescents aged 14 to 18 show that adolescents share emotions on multiple of these platforms. Although the different platforms have similar affordances, their social norms clearly differ and influence adolescents' online behavior. Facebook statuses, Instagram, and Snapchat are mostly used for sharing positive emotions, if emotions are shared at all. Twitter and Messenger, on the other hand, are also used for sharing negative emotions, albeit for different reasons. Highlights: Adolescents often prefer sharing emotions face-to-face, but also share on social media. Platform characteristics, social norms and individual preferences influence medium choice. Facebook statuses, Instagram, and Snapchat are mostly used for sharing positive emotions. Twitter and Messenger are also used for sharing negative emotions.